Sistem Informasi Tanaman Lahan Basah Kebun Raya Sriwijaya - Juairiyah, Oktaf; Maryani, Sri; Komalasari, Oom (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Juairiyah O, Maryani S, Komalasari O. 2019. Wetland information system of Sriwijaya Botanical Garden. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, PalembangÂ 4-5 September 2019. pp. 38-44.Â Palembang: Unsri Press.The Sriwijaya South Sumatra Botanical Garden area is included in the ecoregion of the Sumatran peat swamp forest with the theme of collecting medicinal plants and Sumatra wetlands with several major zones in its development. It is necessary to develop an information database on the Sriwijaya Botanical Garden that provides information on plants that have been planted and the locations that have been planted. The development goal is to design and build a database of wetland plant information systems in the Sriwijaya Botanical Gardens. The methodology used is the System Development Life Cycle (SDLC) and consists of several stages, namely planning, system requirements analysis, system design, implementation, and maintenance. Information systems run on platforms or operating systems that support website-based applications. Consists of two users namely administrator and guest. There are three main menus, namely the planting zone, planting points that have been planted and the types of plants and their benefits. The application displays data and information on plants in the Sriwijaya Botanical Garden.Keywords: database, medicinal plants, wetland, South Sumatra